Beer : what to drink next - Larson, Michael (Sterling Epicure, 2014)
To help beer drinkers find new favorites, this guide organizes ninety beer styles by country of origin and key ingredient, with a brief history of each, three beers to try, suggested food pairings, and recommended breweries.